Relação afetiva entre professora e estudantes do Ensino Superior: sentidos, desafios e possibilidades - Souza, Cleudinéte Ferreira dos Santos (2016)
The research that led to this Master's thesis, developed in the Graduate Education Program of the State University of Feira de Santana, aimed to understand the affective relationship between a teacher and students in the teaching practice, in the context of the Civil Engineering course, having as references its social representations. The study, a qualitative approach in the case study method, was guided by the principles of the Social Representation Theory and in the Complexity Theory. In the collecting and production of the data, we used systematic observation of teaching practice, both in the classroom and in the construction site, and interviews with the use of stimulus question. The observed group consisted of 36 students. Of these, we selected 12 students and the faculty for interviews. The study was referenced in authors such as Ribeiro (2004, 2009, 2010), Moraes (2003), Pinto (2005), Tassoni and Santos (2013), Damasio (2000), among others, to handle on the concept of affectivity, emotion and feeling ; Ribeiro, Jutras and Louis (2005), Veras and Ferreira (2010), Carpim, Behrens and Torres (2014), Freire (1996), Postic (2007) and others to discuss the teaching practice concepts and Moscovici (2003) and Jodelet (2005) to support the Theory of Social Representations; Morin, 2007; Moraes, 2008; Behrens, 2007 to support the Complexity Theory. The Data analysis was inspired by the Bardin Content Analysis (2010). During the analysis three dimensions were identified: a) the affective sense in the educational relationship; b) the challenges of the affective relationship between teachers and students; c) the facing of the challenges of affective relationship in teaching practice. The results show that the meanings attributed by research collaborators in relation to affectivity are linked: to the idea of pleasure in teaching; the teacher's attitudes towards students; the personal qualities of the teacher.The challenges to be faced refers to the promotion of changes in relation to the teacher attitudes with students and to the changes in teaching strategies. With regard to the possibilities to face the challenges, it was evident the need for reflection on the practice itself and the continuing training of higher education teachers. In addition, the results show that the affective teacher is near, supportive, welcoming, cares with the training needs of students, respect cultural differences, is dedicated to the profession, is a friend, has common sense, sensitivity, flexibility and humanity in dealing with cognitive and affective difficulties of students. The main conclusion of this study was that the centrality of the practice of the teacher considered affective is on students learning.